Cerebellar abnormalities in Huntington's disease: A role in motor and psychiatric impairment?. Issue 13 (13th August 2014) - Rees, Elin M.; Farmer, Ruth; Cole, James H.; Haider, Salman; Durr, Alexandra; Landwehrmeyer, Bernhard; Scahill, Rachael I.; Tabrizi, Sarah J.; Hobbs, Nicola Z.
Abstract The cerebellum has received limited attention in Huntington's disease (HD), despite signs of possible cerebellar dysfunction, including motor incoordination and impaired gait, which are currently attributed to basal ganglia atrophy and disrupted fronto‐striatal circuits. This study is the first to investigate a potential contribution of macro‐ and microstructural cerebellar damage to clinical manifestations of HD. T1‐ and diffusion‐weighted 3T magnetic resonance imaging (MRI) scans were obtained from 12 controls and 22 early‐stage HD participants. Manual delineation and voxel‐based morphometry were used to assess between‐group differences in cerebellar volume, and diffusion metrics were compared between groups within the cerebellar gray and white matter. Associations between these imaging measures and clinical scores were examined within the HD group. Reduced paravermal volume was detected in HD compared with controls using voxel‐based morphometry (P < 0.05), but no significant volumetric differences were found using manual delineation. Diffusion abnormalities were detected in both cerebellar gray matter and white matter. Smaller cerebellar volumes, although not significantly reduced, were significantly associated with impaired gait and psychiatric morbidity and of borderline significance with pronate/supinate‐hand task performance. Abnormal cerebellar diffusion was associated with increased total motor score, impaired saccade initiation, tandem walking, and timed finger tapping. In conclusion, atrophy of the paravermis, possibly encompassing the cerebellar nuclei, and microstructural abnormalities within the cerebellum may contribute to HD neuropathology. Aberrant cerebellar diffusion and reduced cerebellar volume together associate with impaired motor function and increased psychiatric symptoms in stage I HD, potentially implicating the cerebellum more centrally in HD presentation than previously recognized. © 2014 International Parkinson and Movement Disorder Society